Peculiarities of archival information resources legal regulation in the field of research on the development of the rocket and space industry - L. M. Popova; А. V. Khromov (Bulletin of Kharkiv National University of Internal Affairs)
It has been noted that in the course of military events on the territory of Ukraine, where the Russian Federation has fired thousands of ballistic and cruise missiles, killing thousands of Ukrainians, interest in the topic of rocket and space technology has increased significantly. The interest of the Ukrainian population in information about the possibilities for the development of the rocket and space industry in Ukraine and its position in the global space services market has grown especially. One of the fundamental problems in the study of the historical development of the rocket and space industry is the closed nature of archival information resources due to the fact that the vast majority of these material carriers of information have access restrictions and are stored in the archival departments of the development organisations, while other documents that lose their technical relevance are destroyed.